Between Conflict and Solidarity: Pandemic Media Coverage of Romanian Intra-EU Labour Migrants - Vincze, Hanna Orsolya (2022)
The Covid-19 pandemic affected Romanian intra-EU labour migrants in a particular way and challenged the established themes associated with and the social roles assigned to them in news discourses. During the first wave of the pandemic, Covid-19 hotspots were reported abroad in Romanian migrant communities, the most notorious example being at the Tönnies factory in Germany. The pandemic brought to prominence the precarious working conditions of labour migrants employed in agriculture and especially in the food industry. Wider discussions, conflicts, and solidarity actions were generated around this topic. In the present study, we identify the main themes and topics present in the Romanian media coverage of Romanian labour migrants, as well as the way foreign, particularly German, media perspectives were integrated into and domesticated in the Romanian coverage. Findings show that both the Romanian and German media used, to a certain extent, the media coverage of this exceptional pandemic situation to invite reflection on the general social costs of migration and on the responsibility of political actors in the migrants’ country of origin, in their country of destination, and at the level of EU institutions. However, the perspective of the migrants was underrepresented in the media coverage.